2016
DOI: 10.1002/ajmg.b.32437
|View full text |Cite
|
Sign up to set email alerts
|

LINE1 insertions as a genomic risk factor for schizophrenia: Preliminary evidence from an affected family

Abstract: Recent studies show that human-specific LINE1s (L1HS) play a key role in the development of the central nervous system (CNS) and its disorders, and that their transpositions within the human genome are more common than previously thought. Many polymorphic L1HS, that is, present or absent across individuals, are not annotated in the current release of the genome and are customarily termed "non-reference L1s." We developed an analytical workflow to identify L1 polymorphic insertions with next-generation sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 61 publications
2
25
1
Order By: Relevance
“…Our findings are consistent with the hypothesis previously introduced by others that altered expression of TEs in human DLPFC may affect the expression of protein-coding genes leading to malfunction of genetic regulatory networks during development as well as during the clinical manifestation of Schizophrenia and other brain disorders in humans ( Chen et al. 2016 ; Guffanti et al. 2016 ; Mills et al.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with the hypothesis previously introduced by others that altered expression of TEs in human DLPFC may affect the expression of protein-coding genes leading to malfunction of genetic regulatory networks during development as well as during the clinical manifestation of Schizophrenia and other brain disorders in humans ( Chen et al. 2016 ; Guffanti et al. 2016 ; Mills et al.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we consider association as a study having shown that a retrotransposon insertion, or insertions, may cause a disease, or the study having reported elevation of retrotransposon copy number or mRNA level in the brain tissue of affected individuals when compared with healthy individuals. retrotransposon neurological disease insertions activity (mRNA levels, CNV, biomarkers) HERV multiple sclerosis [ 166 168 ] 3q13.31 microdeletion syndrome [ 169 ] amyotrophic lateral sclerosis [ 170 , 171 ] multiple sclerosis [ 166 168 , 172 ] schizophrenia [ 173 176 ] bipolar disorder [ 173 , 175 , 177 ] HIV-associated dementia [ 178 ] major depression [ 177 ] autism [ 179 ] ADHD [ 180 ] L1 pyruvate dehydrogenase complex deficiency [ 110 ] Fukuyama-type congenital muscular dystrophy [ 181 ] neurofibromatosis type I [ 182 ] ataxia with oculomotor apraxia 2 [ 183 ] glioblastoma [ 184 , 185 ] schizophrenia [ 176 ] ataxia telangiectasia [ 54 ] Coffin Lowry syndrome [ 186 ] major depression [ 187 , 188 ] schizophrenia [ 187 189 ] Rett syndrome [ …”
Section: Retrotransposition In Neurological Diseasementioning
confidence: 99%
“…L1 retrotransposition, as one of the DNA damaging agents, can lead to various types of genomic instability1718. There is growing evidence that genomic instability can be caused by environmental stress19.…”
Section: Discussionmentioning
confidence: 99%